2006
DOI: 10.1002/crat.200510663
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the starting powders on the synthesis of nickel ferrite

Abstract: The thermal decomposition of freeze-dried nickel(II)-iron(III) formate was investigated by means of DTA, TG, mass spectrometry and X-ray powder diffractometry. For the preparation of homogeneous freeze-dried nickel(II)-iron(III) formate precursors, a rigorous control of nickel ion concentration in the precursor solution was required. The decomposition of the reactive nickel(II)-iron(III) formate does not only reflect aspects of single formates, but also an interaction between components which lowers the decomp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…In the next step, at a temperature above 400 °C, Ni is probably reoxidized. It has been shown that the decomposition of NiF in air at temperatures above 300 °C leads to the formation of a mixture of nickel oxide and metallic nickel [30,31]. The NiN (Figure 1c) decomposes in several steps with a total weight loss of approx.…”
Section: Thermal Decomposition Of Catalysts Precursorsmentioning
confidence: 99%
“…In the next step, at a temperature above 400 °C, Ni is probably reoxidized. It has been shown that the decomposition of NiF in air at temperatures above 300 °C leads to the formation of a mixture of nickel oxide and metallic nickel [30,31]. The NiN (Figure 1c) decomposes in several steps with a total weight loss of approx.…”
Section: Thermal Decomposition Of Catalysts Precursorsmentioning
confidence: 99%
“…Out of all inorganic fillers, ferrite fillers are more crucial due to their stable crystal structure, good magnetic properties, high electrical properties, and the spinel ferrites are widely used in electronic devices, magnetic materials based on them have attracted a lot of attention. [15][16][17][18][19] Because of lowdimensional electrical system applications, nanoscopic sized filler particles are in polymer matrix, such a combination exhibits improved electrical characteristics. Because of their spinel structure, ferrites are a prominent filler material used by scientists for improving the electrical features of pure polymers.…”
Section: Introductionmentioning
confidence: 99%
“…The main advantage of inorganic filling is that it is nontoxic. Out of all inorganic fillers, ferrite fillers are more crucial due to their stable crystal structure, good magnetic properties, high electrical properties, and the spinel ferrites are widely used in electronic devices, magnetic materials based on them have attracted a lot of attention 15–19 . Because of low‐dimensional electrical system applications, nanoscopic sized filler particles are in polymer matrix, such a combination exhibits improved electrical characteristics.…”
Section: Introductionmentioning
confidence: 99%